The Use of Podcasts in Improving Students Listening Skills at University Level - Andi Ainun; Munir; Muh. Tahir (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2024)
The objective of the research was to determine whether there was a significant effect the use of podcasts on the students listening skills. This research was done at Universitas Negeri Makassar. The population of this research was the students from Universitas Negeri Makassar. The researcher used cluster random sampling to choose the sample of the research. The sample of this research was 25 students from class D 2020. The researcher used a quantitative technique. The instrument of this research was a liste ning test using audio podcast which was administered as a pretest and post-test. Based on the result of data analysis showed that the use of audio podcast improved the students listening skill. It was shown by the mean post-test score which was higher than the mean pretest score (63.63>51.76). Then, the researcher concluded that using audio podcasts on the listening skills has a significant effect on students listening skill